2022
DOI: 10.1242/dev.200249
|View full text |Cite
|
Sign up to set email alerts
|

Hyaline cartilage differentiation of fibroblasts in regeneration and regenerative medicine

Abstract: Amputation injuries in mammals are typically non-regenerative, however joint regeneration is stimulated by BMP9 treatment (Yu et al., 2019) indicating the presence of latent articular chondrocyte progenitor cells. BMP9 induces a battery of chondrogenic genes in vivo, and a similar response is observed in cultures of amputation wound cells. Extended cultures of BMP9 treated cells results in differentiation of hyaline cartilage and single cell RNAseq analysis identified wound fibroblasts as BMP9 responsive. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 93 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…The third stage during which a dense condensation takes place to form a disc of unknown structure is the collecting of collagen filaments inside the first step. Yu et al, 2022). The stages of formation in the cephalopods resemble the origin of bone in semi-invertebrates and vertebrates because the Octopus vulgaris is considered an advanced and higher invertebrate (Liu, 2019;Liu et al, 2021;Allen et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third stage during which a dense condensation takes place to form a disc of unknown structure is the collecting of collagen filaments inside the first step. Yu et al, 2022). The stages of formation in the cephalopods resemble the origin of bone in semi-invertebrates and vertebrates because the Octopus vulgaris is considered an advanced and higher invertebrate (Liu, 2019;Liu et al, 2021;Allen et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The hyaline cartilage began to appear in phylum Annelida as a solid capsule, originating from solid epidermal connective tissue, and in echinoderms by lower condensation of collagen fibers, and then differentiated into cephalopod for different types and functions (Bairati et al, 1998;Cole et al, 2004;Whittaker et al, 2006;Brittberg et al, 2008;Cole, 2011;Person, 2012;Owen, 2022). The cephalopods contain different types of hyaline cartilage according to the differentiation and functions of fibroblast cell itself; in addition, they differ from other invertebrates with respect to the formation from lose tissue and the nature of origin from connective tissue (Boyan et al, 1999;Cole et al, 2004a;Hall, 2005;Cole, 2011a;Ehrlich, 2015;Grässel et al, 2016;Irawan et al, 2018;Krings et al, 2022;Ragheb et al, 2022;Yu, 2022). The differential process first appears and condensation in crustaceans passes to top qualification in Mollusca as the first appearance of the cartilage in several tissues of the animal body parts as mantle tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al. ( 77 ) found that BMP-9 could induce fibroblasts to differentiate into hyaline cartilage, and then carried out in vivo experiments to implant hyaline cartilage into acutely damaged joints. It was found that the transplanted hyaline cartilage survived and maintained the hyaline cartilage phenotype after implantation, but did not form mature articular cartilage.…”
Section: The Mechanism Of Fibroblast Regulating Fracture Healingmentioning
confidence: 99%
“…The specific p38 MAPK plays multiple roles in chondrocyte differentiation [ 91 , 92 , 93 ]. It is considered an active regulator in chondrocyte differentiation, as well as chondrogenesis [ 90 ], due to its positive regulation of differentiation of prechondrogenic limb into hyaline chondrocytes which produce hyaline cartilage, the most widespread cartilage that is usually present within joints [ 94 ]. All of the positive influences FGF19 has on cartilage by increasing mitochondrial biogenesis and promoting chondrogenesis provide greater insight into the impacts FGF19 has on chondrocytes and cartilage.…”
Section: Signaling Pathways Involved In Chondrocyte-based Cartilage R...mentioning
confidence: 99%